The Roles of Parents, Health Workers, and Peer in Preventing Youth Premarital Sex Behaviour in Indonesia - Mellysa Kowara; Anastasia Titisari; Luh Kadek Ratih Swandewi (Warmadewa University, 2024)
Adolescents are a vital component in the nation's development for the future, comprising 10% of the total population aged 15-24 years old. However, many adolescents are engaging in premarital sex, which contributes to various adverse effects including an increased risk of contracting STIs, HIV/AIDS, unintended pregnancies, and more. This study aims to analyze the roles of parents, peers, and healthcare providers in providing sexual education to prevent premarital sex among adolescents. Using a cross-sectional approach, the study analyzed the role of parents, healthcare workers, and peers in sexual education and its influence on premarital sexual behavior. The research was conducted in nine districts in Bali Province, with a total sample size of 455 individuals. The results revealed that the majority of adolescents consider sexual and reproductive health education important but feel uncomfortable discussing it, particularly with their parents. The absence of parental involvement was indicated by other findings, as only the roles of healthcare workers and peers were significantly associated with a history of receiving sexual education. The role of parents as the primary source of sexual education and guidance can be enhanced through training and education to improve their understanding of adolescent reproductive counseling. This would foster a sense of comfort and openness in discussing the sexual and reproductive issues experienced by adolescents.